Research on the Value Foundation and Transmission Path of the Concept of a Community with a Shared Future for Mankind in Pakistan - Wang, Yan (Pacific International Journal, 2025)
This paper delves deep into the value foundation and practical path of the concept of a community with a shared future for mankind in Pakistan. By integrating cross-cultural communication theory, this paper proposes the construction of a “multi-level, multi-subject” communication network, aiming to provide valuable reference for the regionalization practice of international concepts. Extensive research has revealed that the dissemination of this concept in Pakistan is firmly anchored in the political mutual trust stemming from the all-weather strategic partnership between China and Pakistan, the economic cooperation ties forged by the China Pakistan Economic Corridor (CPEC), and the interactive foundation between Pakistan civilization and traditional Chinese culture. The transmission path in this paper encompasses a wide array of multidimensional channels, including educational cooperation, media narrative, public diplomacy, and digital platforms. Through in-depth analysis, the author shows that the CPEC project not only drives infrastructure development but also significantly deepens the recognition of the “common interest view” among the Pakistani people through rich cultural exchanges.